Design System e-Culinary Website-Based for Small Medium Enterprises - Albertin Parupang; John Reimon Batmetan (International Journal of Information Technology and Education, 2022)
Information technology has experienced significant developments in the last few decades. There are many technology options that can increase the convenience and benefits of small and medium-sized businesses. One of the activities that can utilize information technology is in the field of marketing and sales to build a business. In many areas in developing countries there are small and medium enterprises (SMEs) most of which still use traditional methods for marketing and sales. The purpose of this research is to design a Web-based e-culinary system for Small and Medium Enterprises as a Media to Support Marketing and Sales. The results of this study show that the e-culinary system can be designed based on a website with software engineering tools. As a result, an e-culinary system can be built that can help SMEs increase their income. This system is expected to support marketing and sales for SMEs in the region.